The Influence of Capital Adequacy Ratio, Loan to Deposit Ratio, and Net Interest Margin on Return on Asset at Bank Jabar Banten - Sari, Widya; Putri, Nur Azizah Hasna; Apriani, Dina (International Journal of Global Operations Research, 2023)
Based on the results of observations, this research is motivated by the fluctuating phenomenon in these ratios and the discrepancy with the theory put forward by experts. This study aims to find out how the effect of CAR on ROA at Bank BJB, find out how the influence of LDR on ROA at Bank BJB, find out how the influence of NIM on ROA at Bank BJB, and find out how the influence of CAR, LDR, and NIM simultaneously on ROA at Bank BJB. The object of research in this thesis is the ratio of CAR, LDR, and NIM to ROA. The type of research is quantitative with an associative approach with secondary data types and uses data collection techniques in the form of documentation and literature study. While taking the sample using purposive sampling technique. The population is Bank BJB quarterly financial report data for the 2017-2021 period. The results of the study show that there is no significant and negative effect between CAR on ROA at Bank BJB, there is no significant effect between LDR on ROA at Bank BJB and in a negative direction, but there is a significant effect between NIM on ROA at Bank BJB.Â  Simultaneously there is no effect between CAR, LDR, and NIM on ROA at Bank BJB.